Knowledge, Attitude And Adherence To Taking Blood Supplement Tablets Against Anemia In Adolescent Girls - Rehana Rehana; Nurul Komariah; Heni Listriana (CV. AFDIFAL MAJU BERKAH, 2024)
Young women's lack of knowledge about anemia and the benefits of low blood pressure, will affect young women's compliance in taking iron tablets as recommended by health workers. Prevention of anemia can be done by improving the behavior of young women in preventing anemia. Research objectives: Knowledge, attitude and adherence to taking iron tablets in young women with anemia at SMP Negeri 12 Palembang. This type of research is descriptive analytic with the Cross Sectional method where the researcher analyzes the relationship between the dependent variable and the independent variable with various approaches at one time, the sample used is 60 female students taken by purposive sampling method, data collection is done by filling out a questionnaire. There is a significant relationship between knowledge and the incidence of anemia in young women with a p-value = 0.037 and OR = 4.342. There is a significant relationship between attitude and the incidence of anemia in young women with a p-value = 0.054 and OR = 8.357. There is a significant relationship between compliance with the incidence of anemia in young girls at SMPN 12 with a p-value = 0.041 and OR = 3.953. Conclusion: There is a significant relationship between Knowledge, Attitude and Compliance with the incidence of anemia in young women in junior high school.